Four Tomato FLOWERING LOCUS T-Like Proteins Act Antagonistically to Regulate Floral Initiation - Cao, Kai; Cui, Lirong; Zhou, Xiaoting; Ye, Lin; Zou, Zhirong; Deng, Shulin (Frontiers in Plant Science, 2016)
The transition from vegetative growth to floral meristems in higher plants is regulated through the integration of internal cues and environmental signals. We were interested to examine the molecular mechanism of flowering in the day-neutral plant tomato (Solanum lycopersicum L.) and the effect of environmental conditions on tomato flowering. Analysis of the tomato genome uncovered 13 PEBP (phosphatidylethanolamine-binding protein) genes, and found six of them were FT-like genes which named as SlSP3D, SlSP6A, SlSP5G, SlSP5G1, SlSP5G2 and SlSP5G3. 6 FT-like genes were analyzed to clarify their functional roles in flowering using transgenic and expression analyses. We found that SlSP5G, SlSP5G2 and SlSP5G3 proteins were floral inhibitors whereas only SlSP3D/SFT (SINGLE FLOWER TRUSS) was a floral inducer. SlSP5G was expressed at higher levels in long day (LD) conditions compared to short day (SD) conditions while SlSP5G2 and SlSP5G3 showed the opposite expression patterns. The silencing of SlSP5G by VIGS (Virus induced gene silencing) resulted in tomato plants that flowered early under LD conditions and the silencing of SlSP5G2 and SlSP5G3 led to early flowering under SD conditions. The higher expression levels of SlSP5G under LD conditions were not seen in phyB1 mutants, and the expression levels of SlSP5G2 and SlSP5G3 were increased in phyB1 mutants under both SD and LD conditions compared to wild type plants. These data suggest that SlSP5G, SlSP5G2 and SlSP5G3 are controlled by photoperiod, and the different expression patterns of FT-like genes under different photoperiod may contribute to tomato being a day neutral plant. In addition, PHYB1 mediate the expression of SlSP5G, SlSP5G2 and SlSP5G3 to regulate flowering in tomato.